The Design and Construction of an Automatic and Android Controlled Change Over Switch. - Turyasingura Gideon (Kabale University, 2023)
Consumers of power in developing countries have been faced with electricity challenges which have resulted in economic retardation, poor gross domestic products and weak industrialization. This project looks at a method to improve power stability and reliability. To achieve this, alternative power sources that works efficiently with minimum time delay is required. The automatic change over switch with a remote-control capability effectively solves the problem of uninterrupted power supply. This project is designed to automatically supply continuous power to the load through one of the three sources of supply that is, mains, generator, and Inverter, with priority in that order. Arduino is used as the controller to the entire system. Relay controlled by the Arduino are used to switch power supply between the different sources to load depending on the availability and priority. A lamp is used as a load for demonstration purpose. An LCD was used in displaying the source that is connected to the load. A GSM modem controlled by the Arduino is also used to remotely control the switches.